Assessing impacts of social-ecological diversity on resilience in a wetland coupled human and natural system - Nathan D. Van Schmidt (Resilience Alliance, 2021)
Theory posits that resilience of ecosystems increases when there is a diversity of agents (e.g., species) and linkages between them. If ecosystems are conceptualized as components of coupled human and natural systems, then a corollary would be that novel types of human-induced diversity may also foster resilience. We explored this hypothesis by studying how socially created diversity mediated the impact of a historically severe drought on a network of wetlands in the foothills of the California Sierra Nevada containing a metapopulation of the threatened California Black Rail (Laterallus jamaicensis coturniculus). We examined how (1) diversity in motivations for land ownership affected use of irrigation water and response to drought; (2) differences in natural and irrigated water sources affected wetland drying in response to drought; and (3) these processes affected the persistence of rails and the transmission risk of West Nile virus (WNV), an emerging infectious disease that threatens people and rails. Wetlands were mostly fed by inefficiencies and leaks from the irrigation system. Wetlands with both natural and irrigated water sources were larger, wetter, and likelier to persist through drought because these two sources showed response diversity by drying at different times. Wetlands with diverse water sources also provided the best habitat for the California Black Rail, and irrigation appeared responsible for its persistence through the drought. Irrigation increased WNV transmission risk by increasing the quantity, but not the quality, of wetland habitats for mosquitoes. The impacts of social diversity were more ambiguous, with redundancy prevalent. However, profit-motivated landowners provided wetlands more irrigation during nondrought conditions, whereas other landowner types were more likely to continue providing irrigation during drought. Our results highlight that conservation in social-ecological systems requires assessing not only the value of historic ecological diversity, but also how novel types of socially induced diversity may benefit ecosystems.